LEGAL PROTECTION FOR DOCTORS AND PATIENTS IN HEALTH SERVICES IN INDONESIA - Rivaldi Pratama Haryanto (LEX SOCIETAS: Journal of Law and Public Administration, 2025)
The relationship between doctor and patient is a relationship based on the law. Practically, both doctor and patient have the same potential to experience loss or disadvantages due to one of the parties violate the obligations and rights. Treatment of disease that involves two parties – the health service provider and the patient should be protected by law. It is to embody the highest degree of health for the community in order to achieve a strong, healthy, and productive nation. The aim of this writing is to know all matters concerning the state regulation of relationship between doctor and patient, including each party’s obligations and rights as well as legal protection for both doctor and patient. Method of this writing is qualitative descriptive by collecting data and information based on health laws in Indonesia, as well as literature research. Other source of data and information are from relevant writing such as scientific journal, thesis, books and other electronic media.Increasing public knowledge about the health of the increasing criticism and demands on health services provided by health providers, application and utilization of health law at this time is not maximized, this proved not their field or special sections health care law itself both in the hospital and health services other. The negative impact is still an element of discrimination among health professions, the incidence rate is still high malpractice as was the case recently occurred, the patient died in Jakarta Chiropractic Clinic and the rampant cases of trade in human organs. With the increasing incidence of malpractice so prevention is indispensable to the health law priority in health services in hospitals based on values of justice